A longitudinal study on the impact of species and age of animals on milk production in dairy animals - Chaudhary, J K; Verma, M R; Kshandakar, Shashank (Indian Journal of Dairy Science, 2020)
A longitudinal study was conducted to assess the impact of species and age of animals on milk production in dairy animals. The longitudinal data on milk yield of cattle and buffaloes have been recorded fortnightly interval up to 300 days for the period 2005 to 2014 from the dairy farm of Indian Veterinary Research Institute (IVRI), Izatnagar, Bareilly, Uttar Pradesh. From the study we found that the base line milk yield was significantly (p value<.0001) higher in cattle than buffaloes. The change in milk yield decreases with time and this decrement was more in buffaloes than cattle. After adjusting for baseline age, on average cattle baseline milk yield was about 1.05 units more than buffaloes and after adjusting for species, one year increase in age corresponds to 0.102 unit increases in baseline milk yield. Cattle milk yield change rate was about 0.0009 units greater than buffaloes after adjusting for baseline age and one year increase in age corresponds to 0.0012 units less in milk yield change rate after adjusting for species.